Out-of-plane analysis of dry-stone walls using a pseudo-static experimental and numerical approach in scaled-down specimens - Santa-Cruz S. (2021)
This research was developed under the support of the CONCYTEC with the contract N°109-2017-FONDECYT : “Validación de técnicas de construcción de pircas mediante estudios numérico-experimentales con tecnología desarrollada en Perú”. The authors also thank to the University Grenoble-Alpes and Laboratory Soils Solids Structures and Risk for the use of 3DEC software during the stay of one of the authors in the laboratory at Grenoble.